Strengthening Consumer Legal Protection Related to Real Estate Marketing in Pre-Project Selling - Anitya Maharani, Ni Putu; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
AbstrakIn recent years, housing and property development in Indonesia has seen a rapid increase, accompanied by the growing population. Pre-project selling is a strategy where developers sell real estate before construction is completed or even before it begins. This system involves offering consumers concepts, images, and information related to size, location, and promised facilities. Although this method helps developers reduce construction costs, it poses legal risks for consumers, such as design discrepancies, material quality issues, changes in specifications, and delays in obtaining building permits. To protect consumers, the Sales and Purchase Binding Agreement (PPJB) is used as a legal instrument that binds the rights and obligations of both parties, providing legal certainty in real estate transactions. The main focus of the research is to ensure consumer rights protection through the proper application of PPJB in accordance with applicable legal regulations.